Encouraging participative consumerism through evolutionary digital marketing emerging research and opportunity - Kaufmann, Hans Rüdiger 1958-; Manarioti, Agapi 1979- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series, 2017)
"This book focuses on participative consumerism through evolutionary digital marketing. It covers topics such as e-marketing, technology and the internet as a market tool, consumer engagement on social media platforms, the role of content management in online market, integrated online-offline marketing design, multi-channel marketing, dig data, and other topics"--